Matan Hadith Criticism Method - Nazwa Amalia; Mujiyo Mujiyo (Gunung Djati Conference Series, 2021)
This study aims to discuss the method of criticism matan hadith. This research is a qualitative type through literature study by applying content analysis. The results and discussion of this study include general views of criticism, criticism of hadith, and methods of criticism of hadith. This study concludes that the criticism of matan hadith is an attempt to select in the form of research and assessment of the matan hadith which determines the quality of a hadith with several methods. The first method during pre-codification of the hadith, which is comparing the content of the hadith with the verses of the Qur'an, is still possible for post-codification criticism. Meanwhile, if the comparison method is carried out by meeting the narrators directly, it is impossible to apply it to the post-codification critique method. This research is expected to have beneficial implications for the enrichment of Islamic knowledge treasures.